IMPLEMENTATION OF TAHFIDZ ALQURAN LEARNING PADANG ISLAMIC BOARDING SCHOOL - Sukrisman Sukrisman; Muhammad Kosim; Syafruddin Syafruddin (STKIP Pesisir Selatan, 2023)
This research is motivated by the fact that shows that there is great attention to learning tahfidz Alquran in formal, non-formal and informal education channels. Various efforts have been made to create memorizers of the Alquran so that there are those who make learning tahfidz Alquran a superior or mandatory extracurricular program, namely at the Ar-Risalah Islamic College and Islamic Boarding School in Minangkabau Village, in Padang. The limitations of the problem in this study are how to plan tahfidz Alquran learning, how to implement tahfidz Alquran learning and how to evaluate learning tahfidz Alquran at Islamic boarding schools in Padang. The purpose of this study was to determine the learning strategies for tahfidz Alquran in the aspects of lesson planning, implementation of learning and evaluation of tahfidz Alquran learning at Islamic boarding schools in Padang. This study succeeded in finding i) Learning planning for tahfidz Alquran at Ar-Risalah Islamic College and Islamic Boarding School in the Minangkabau village of Padang, namely formulation learning objectives, preparation of students, preparation of educators, preparation of materials, methods, media and learning resources as well environment. ii) Implementation of learning tahfidz Alquran at the Ar-Risalah Islamic College and Islamic Boarding School in the Minangkabau village , namely the implementation of learning objectives as evidenced by the seriousness of student, the arrangement of materials, methods, use of media and learning resources along conditions of the learning environment. iii) Evaluation of learning tahfidz Alquran at Ar-Risalah Islamic College and Islamic Boarding Schools at Minangkabau villages is carried by way of formative evaluation, which is carried out at the end of the semester and the of the year, summative evaluation is carried out at each meeting and reporting of learning result at the end of each year.